O nieperyfrastycznych nominacjach Stalina - Zemszał, Piotr (Przegląd Rusycystyczny, 2009)
SOME WORDS ABOUT NONCIRCUMLOCUTIONAL NOMINATIONS OF STALIN Summary The paper focuses on the pragmatic analysys of noncircumlocutional nominations of Joseph Stalin, that were used in the soviet paper “Pravda” between 1945 and 1947: Stalin, tovarishch Stalin and Joseph Vissarionovich Stalin. The article shows most typical contexts, in which individual nominations appears and depends of using them. In the article are shown and discussed differences between individual noncircumlocutional nominations and scope of their functions. О НЕПЕРИФРАСТИЧЕСКИХ НОМИНАЦИЯХ СТАЛИНА Резюме В статье дается прагмалингвистический анализ неперифрастических номинаций Ио-сифа Сталина, которые употреблялись в советской газете «Правда» в период 1945–1947: Сталин, товарищ Сталин и Иосиф Виссарионович Сталин. В статье указаны наиболее характерные контексты, в которых выступают эти номинативные единицы и обсуж-дены условия их употребления, показаны и обсуждены различия между отдельными неперифрастическими номинациями и области их функционирования.